2006
DOI: 10.1080/00207140600689496
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotic Conflict: A Brief Report

Abstract: Two studies investigated management of conflict in hypnosis by subtly increasing the brightness of a visual stimulus during a suggestion for hypnotic blindness to the stimulus. In Study 1, 23 high hypnotizable participants were administered a hypnotic suggestion for blindness to a projected light. For half the participants, the brightness of the light was intensified during the suggestion. Behavioral ratings and online analog-dial measurement indicated that participants reported decreased hypnotic blindness du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The finding is also consistent with research that has found that a proportion of highs experiencing a hypnotic delusion (Noble and McConkey, 1995; Cox and Barnier, 2009) or posthypnotic amnesia (Kihlstrom et al, 1980; McConkey and Sheehan, 1981; Coe, 1989; Coe and Sluis, 1989) breach their experience in response to challenges. Hypnotic effects require participants to resolve the conflict between objective reality and the suggested experience (McConkey, 1983; Mallard and Bryant, 2006). Challenges both draw attention to and increase this conflict, leading some participants to breach the suggested effect.…”
Section: Discussionmentioning
confidence: 99%
“…The finding is also consistent with research that has found that a proportion of highs experiencing a hypnotic delusion (Noble and McConkey, 1995; Cox and Barnier, 2009) or posthypnotic amnesia (Kihlstrom et al, 1980; McConkey and Sheehan, 1981; Coe, 1989; Coe and Sluis, 1989) breach their experience in response to challenges. Hypnotic effects require participants to resolve the conflict between objective reality and the suggested experience (McConkey, 1983; Mallard and Bryant, 2006). Challenges both draw attention to and increase this conflict, leading some participants to breach the suggested effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that conflicting reality information interferes with some hypnotic participants' ability to experience a suggestion (Bryant & McConkey, 1989. For example, in a study of hypnotic blindness, Mallard and Bryant (2006) found that increasing the brightness of a visual stimulus during hypnosis led to participants reporting decreased hypnotic blindness. It thus seems that successful suggestions need to prepare participants that they will be looking at a mirror even if they do not recognise it as such.…”
Section: Comparing the Suggestions For Mirror Agnosiamentioning
confidence: 98%
“…Hypnosis is not psychotherapy. Hypnotic perceptual and cognitive changes the equilibrium between suggestion, expectation, and task instructions [47][48][49].…”
Section: Mechanismmentioning
confidence: 99%